2021
DOI: 10.1017/cjn.2021.52
|View full text |Cite
|
Sign up to set email alerts
|

Claw Toe: Anatomic Guide for Injection of Botulinum Toxin into Foot Muscles

Abstract: Background: Poor response to injection of botulinum toxin (BoNT) into the flexor digitorum longus (FDL) muscle has been reported especially in patients with claw foot deformity. We previously advocated BoNT injection into the flexor hallucis longus (FHL) muscle in such patients. Here, we determined the functional and anatomical relationships between FHL and FDL. Methods: Toe flexion pattern was observed during electrical stimulation of FHL and FDL muscles in 31 post-stroke patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…In this study, we categorized the dominant type of the FHL and FDL muscles for each toe by analyzing the results of multiple sessions in patients who underwent repeated electrical stimulations. The results showed fewer type IIs and more type III to type V in FHL compared to the findings of previous studies [ 1 , 2 ]. The insertion of the FHL muscle into each toe naturally affects the big toe, but it also affects the second and the more peroneal toes.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…In this study, we categorized the dominant type of the FHL and FDL muscles for each toe by analyzing the results of multiple sessions in patients who underwent repeated electrical stimulations. The results showed fewer type IIs and more type III to type V in FHL compared to the findings of previous studies [ 1 , 2 ]. The insertion of the FHL muscle into each toe naturally affects the big toe, but it also affects the second and the more peroneal toes.…”
Section: Discussioncontrasting
confidence: 52%
“…Although the above ratios varied in individual studies, the majority reported a pattern of tendon binding from FHL to FDL. In our previous studies [ 1 , 2 ], the dissection of six cadavers (twelve legs) showed that the FHL tendon bifurcated and joins the FDL in all of them, while there was no tendon coupling from the FDL to the FHL ( Figure 2 a–d). In one previous study examining the cadavers’ Knots of Henry in 16 limbs [ 13 ], contraction of the FHL in 11 limbs resulted in not just the big toe motion but the second toes as well as the toes on peroneal side, while contraction of the FDL induced no flexion of the big toe.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations